Mountains of fire : the menace, meaning, and magic of volcanoes - Oppenheimer, Clive (The University of Chicago Press, 2023)
"Volcanologist and filmmaker Clive Oppenheimer offers here a seemingly impossible tour, showing readers places difficult to access, even before one considers climbing a volcano. Oppenheimer worked closely with North Korean researchers in a scientific mission to study Mount Paektu, a volcano name sung in national anthems on both sides of the Demilitarized Zone. He ventured through Chad to the Tibesti Mountains; their most emblematic volcano, Emi Koussi, is the highest point in the Sahara and has a caldera colossal enough to enclose a city the size of Boston. He has voyaged south to the hottest place on the coldest continent, studying gases emitted from Antarctica's Mount Erebus. This geographic range is matched by the diversity of subjects that Oppenheimer examines to reveal how entangled volcanic activity is with our climate and environment, as well as our economy, politics, culture, and beliefs. These adventures and investigations make clear the dual purpose of volcanology--both to understand volcanoes for science's sake and to serve the communities endangered and entranced by these mountains of fire. Readers learn of historic voyages to these enigmatic places and travel alongside Oppenheimer, peering from the crater's edge with assorted monitoring devices, climbing toward the summit to compare the volcano itself to images captured safely from space, hunting for the far-flung deposits of Earth's greatest eruptions, and meeting with others who live with volcanoes. With each measurement and conversation, Oppenheimer shows the importance of listening to experts, communities, and the Earth"--